2022
DOI: 10.4000/chinaperspectives.14060
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Development in Hong Kong: An Ethical Analysis

Abstract: Like many cities in advanced economies, Hong Kong has embraced the "smart city" agenda. In this article, we engage with a number of ethical issues surrounding smart city development. We assess the ethical implications of four different smart city initiatives in Hong Kong -the use of a facial recognition system, the Smart Lamppost Pilot Scheme, the Free-flow Tolling System, and Electronic Health Records System -from the perspective of relational egalitarianism. Our analysis suggests that there are various moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This literature was originally narrow in scope, with a focus on the application of Miller (1974). Levi and Stoker (2000), Gilley (2006), Blind (2007), Grimmelikhuijsen et al (2013), Netelenbos (2016) (Chatterjee et al, 2017;Khan et al, 2017;Braun et al, 2018;Anwar et al, 2020;Julsrud and Krogstad, 2020;Tyagi et al, 2020;Cole and Tran, 2022;Ip and Cheng, 2022;Spicer et al, 2023). Issues examined include security and privacy, ethical dimensions of surveillance, creation of public value through digitization of public services, and the ability of technology to facilitate productive state-society interactions in smart city governance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This literature was originally narrow in scope, with a focus on the application of Miller (1974). Levi and Stoker (2000), Gilley (2006), Blind (2007), Grimmelikhuijsen et al (2013), Netelenbos (2016) (Chatterjee et al, 2017;Khan et al, 2017;Braun et al, 2018;Anwar et al, 2020;Julsrud and Krogstad, 2020;Tyagi et al, 2020;Cole and Tran, 2022;Ip and Cheng, 2022;Spicer et al, 2023). Issues examined include security and privacy, ethical dimensions of surveillance, creation of public value through digitization of public services, and the ability of technology to facilitate productive state-society interactions in smart city governance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These early studies provided a foundation for deeper scholarly examinations of public trust in the context of smart cities. This line of inquiry has since been carried forward in numerous studies, as shown in Table 1 (Chatterjee et al, 2017; Khan et al, 2017; Braun et al, 2018; Anwar et al, 2020; Julsrud and Krogstad, 2020; Tyagi et al, 2020; Cole and Tran, 2022; Ip and Cheng, 2022; Spicer et al, 2023). Issues examined include security and privacy, ethical dimensions of surveillance, creation of public value through digitization of public services, and the ability of technology to facilitate productive state-society interactions in smart city governance.…”
Section: Literature Reviewmentioning
confidence: 99%